Arrival of the Asian tiger mosquito, Aedes albopictus (Skuse, 1895) in Vienna, Austria and initial monitoring activities. Issue 6 (7th June 2021) - Bakran‐Lebl, Karin; Zittra, Carina; Harl, Josef; Shahi‐Barogh, Bita; Grätzl, Andreas; Ebmer, David; Schaffner, Francis; Fuehrer, Hans‐Peter
Abstract: Aedes albopictus was recorded in Vienna, Austria, in August 2020 for the first time. The species was found to occur in three sites within the city; morphology‐based monitoring was followed by DNA‐barcoding. Mitochondrial COI barcode sequences recovered three different haplotypes, however this data does not reveal whether single or multiple introduction events have occurred. The vicinity of Viennese Ae. albopictus sites to major traffic routes highlights the importance of passive transport for range expansion of this species.